An Empirical Study: Causes and Measures for Road Accident from Perspective of State Owned Transport Corporation in India - Karthikeyan, K.; Sakthivel, S. (Gyan Management Journal, 2010)
Road accidents are one of the most crucial problems being faced by modern societies. Incidentally, India ho the dubious distinction of registering the highest number of road accidents in the world. The purpose of paper is to identify the major factors responsible for road accidents and measures taken by the organization government to reduce it. Primary data was collected by the researcher with the help of a structu questionnaire administered to bus drivers of Tamil Nadu State Transport Corporation, Tiruchirapp (TNSTCJ, Tamil Nadu. Convenient sampling has been employed with the questionnaire being collected from 2 respondents. Using various statistical tools like 1) Factor Analysis and 2) Mean Score, the findings will be use,· to identify the causes for road accident and measures to reduce them. So this study becomes more relevant a. significant to the present Indian scenario.
Keywords: Road Accident; Training; Safety Measures; Counseling